2016
DOI: 10.1177/1359105315603473
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of older adults living with an appearance altering burn injury: An exploratory qualitative study

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk UWE makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Additionally, psychological reasons for the increased risk for MH problems can include self-esteem and body image issues. Research reports that burn survivors struggle with unwanted and often distressing social reactions all throughout their life [ 36 38 ]. A recent review of the psychological effects of childhood burns estimated that between 25 and 30% of preschool children experienced significant traumatic stress reactions during the first month post-burn [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, psychological reasons for the increased risk for MH problems can include self-esteem and body image issues. Research reports that burn survivors struggle with unwanted and often distressing social reactions all throughout their life [ 36 38 ]. A recent review of the psychological effects of childhood burns estimated that between 25 and 30% of preschool children experienced significant traumatic stress reactions during the first month post-burn [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research reports that burn survivors struggle with unwanted and often distressing social reactions all throughout their life [ 36 38 ]. A recent review of the psychological effects of childhood burns estimated that between 25 and 30% of preschool children experienced significant traumatic stress reactions during the first month post-burn [ 36 ]. For school-aged children, these rates have been reported to be a lot lower within the same time period, with rates reported to be 3–5% 3 months post-burn [ 39 ] and behavioural rates have been reported as normal in other studies [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…811 Most follow-up investigations are on burn patients, which also suffer from an altered physical appearance. 1215 The purpose of our study is to report about the midterm outcomes of patients who survived NF using two standardized outcome scores.…”
Section: Introductionmentioning
confidence: 99%
“…Adjusting to burns can be challenging ( Jones et al, 2017 ). The few qualitative studies that have been conducted showed that children report changes on the emotional, behavioral, and social level.…”
Section: Introductionmentioning
confidence: 99%